"Entrenching nostalgia" : the historical significance of battlefields for South African tourism (Historia, 2021)
Many famous battles have left legacies and these have often created a sense of nostalgia motivating people to visit associated sites. Battlefields and other sites of "death and decay" have increased as a popular sub-sector of the fast growing heritage and cultural tourism industry. Battlefields, and other sites associated with war, have been studied by scholars from a variety of disciplines. In more recent times, tourism professionals and academics have begun to study battlefields and their associated histories for the purpose of developing and promoting them as tourist attractions. This has resulted in a distinct link between the historical and tourism sectors. In this paper, the Battle of Spioenkop (KwaZulu-Natal) will be discussed as an example of how history and a battle site in particular can contribute to the development of tourism.  Menige bekende veldslae het nalatenskappe gelaat wat dikwels 'n gevoel van nostalgie skep en mense motiveer om verwante terreine te besoek. Slagvelde en ander plekke van "dood en verval" het 'n toenemende gewilde sub-sektor van die vining-groeiende erfenis- en kulturele toerisme-industrie geword. Slagvelde en ander plekke wat verband hou met oorlog, word deur geleerdes van 'n verskeidenheid dissiplines bestudeer. Toerisme-spesialiste en akademici het onlangs begin om slagvelde en die gepaardgaande geskiedenis te bestudeer vir die ontwikkeling en bevordering van die slagvelde of terreine as toeristeaantreklikhede. Dit het gelei tot 'n tasbare verband tussen die historiese en toerisme-sektore. In hierdie studie sal die Slag van Spioenkop (KwaZulu-Natal) bespreek word as 'n voorbeeld van hoe die geskiedenis, en 'n veldslag-terrein in die besonder, kan bydra tot die ontwikkeling van toerisme.
Keywords: Battlefields Route; Slagveldroete; Dark tourism; Heritage